1657 Trauma imaging appropriateness in paediatric patients conveyed to a trauma unit compared to a major trauma centre – a retrospective observational study. Issue 12 (22nd November 2022) - Hibberd, Owen; Price, James; Laurent, Amy; Agrawal, Shruti; Barnard, Edward
Abstract : Aims, Objectives and Background: Appropriate and timely imaging improves trauma outcomes. In adults, the default is whole-body computed tomography (CT). However, in children more selective imaging should be used. In those requiring CT, the national standard is imaging ≤30mins of arrival. The aims of this study were to compare appropriateness of CT and time to initial CT in paediatric trauma patients conveyed directly to a major trauma centre (MTC) with those initially treated in a trauma unit (TU) and then transferred to an MTC. Method and Design: A retrospective observational study in the East of England MTC (2015–2020). All paediatric trauma patients meeting Trauma Audit Research Network (TARN) criteria who arrived at the MTC ≤24hr of injury and underwent CT imaging within 12 hours of arrival were included. Data were obtained from the MTC trauma office and clinical records were independently reviewed by two authors. The Royal College of Radiologists guideline for paediatric trauma was used to assess the appropriateness of the CT imaging strategy.Combined data were stored in a Microsoft Excel sheet and analysed in Prism 9 for macOS (GraphPad). Data are reported as number (percentage), and median [inter-quartile range]. Proportions were compared with a Fisher's Exact test; differences between median values were compared with a Mann-Whitney U test. Results and Conclusion: In the study period n=315 patients were identified. 229 (72.7%) underwent CT <12hrs and were included in the analysis: n=93 MTC, n=136 TU, table 1 . CT imaging was judged as appropriate in n=77/93 (82.8%) MTC and n=104/136 (76.5%) TU scans, p=0.32. The median time to first CT was 35.0 [26.0–75.0] minutes MTC, and 76.0 [48.0–109.0] minutes TU, p<0.0001. We have demonstrated room for improvement in paediatric CT trauma imaging appropriateness across the network, but this is not significantly different between the MTC and TUs. However, time to initial trauma CT was significantly shorter in the MTC.